Comprehensive Physiology 1983
DOI: 10.1002/cphy.cp020327
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Adjustments to Thermal Stress

Abstract: The sections in this article are: Critique of Some Methods Employed in Humans Total and Regional Cutaneous Blood Flow Cardiac Output Central Blood Volume Regional Blood Flow Measurement of Temperature General Features of the Cutaneous Circulation: A Brief Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 355 publications
4
92
1
2
Order By: Relevance
“…Some studies reported an increase in cardiac output in man (Rowell, 1974(Rowell, , 1983, dog (Hales & Dampney, 1975), ox (Whittow, 1965), or chicken (Whittow et al 1964) exposed to high ambient temperatures, whereas no change was observed in the baboon (Hales et al 1979) or sheep (Hales, 1973a). It is of importance to note that those experiments were all performed with animals under acute heat stress, which differs from our study performed with warm-acclimated pigs.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Some studies reported an increase in cardiac output in man (Rowell, 1974(Rowell, , 1983, dog (Hales & Dampney, 1975), ox (Whittow, 1965), or chicken (Whittow et al 1964) exposed to high ambient temperatures, whereas no change was observed in the baboon (Hales et al 1979) or sheep (Hales, 1973a). It is of importance to note that those experiments were all performed with animals under acute heat stress, which differs from our study performed with warm-acclimated pigs.…”
Section: Discussioncontrasting
confidence: 60%
“…Most mammals increase their peripheral blood flow at high ambient temperatures to transfer heat through sensible (conduction, convection and radiation) or evaporative heat loss, depending on the efficiency of sudoriparous glands. For instance, in man, skin blood flow is increased at the expense of blood flow to the kidneys, viscera and skeletal muscles (Rowell, 1974(Rowell, , 1983(Rowell, , 1986. This redistribution of blood flow to the skin is usually less pronounced in panting animals like sheep, dogs (Hales, 1973a;Hales & Dampney, 1975) or pigs, which could explain the observation that skin FCO was only increased for the back of piglets and not for the left leg (a tendency for increase was observed for the ear skin).…”
Section: Discussionmentioning
confidence: 99%
“…When there is thermal stress (i.e., heat and cold) caused by external factors (e.g., increased temperature or humidity) or internal factors (e.g., food intake), human body responds and the thermoregulation system adjusts heat dissipation to the external environment by modifying the blood flow via cutaneous arterioles and veins, causing sweating or shivering [30]. Accordingly, resting skin blood flow in the arterioles in normothermic conditions is approximately 250 mL/min (about 5% of the cardiac output [31]), which results in a heat dissipation of about 80 to 90 kcal/h (~ the level of resting metabolic heat production) [32]. In response to the heat stress, thermoregulatory vasodilation can increase skin blood flow up to 6 to 8 L/min [33] and utilize up to 60% of cardiac output [31].…”
Section: Skin Blood Flow Variations In Response To Thermal Stressesmentioning
confidence: 99%
“…Accordingly, resting skin blood flow in the arterioles in normothermic conditions is approximately 250 mL/min (about 5% of the cardiac output [31]), which results in a heat dissipation of about 80 to 90 kcal/h (~ the level of resting metabolic heat production) [32]. In response to the heat stress, thermoregulatory vasodilation can increase skin blood flow up to 6 to 8 L/min [33] and utilize up to 60% of cardiac output [31]. In response to the cold stress, thermoregulatory vasoconstriction can limit the skin blood flow to approach zero.…”
Section: Skin Blood Flow Variations In Response To Thermal Stressesmentioning
confidence: 99%
“…A patient going into shock redistributes the blood volume from the peripheral to the central circulation. The skin is an important organ in regard to circulatory homeostasis variably absorbing 5-70 % of the cardiac output [4]. Application of a firm blanching pressure to the skin with subsequent observation of the return of blood flow to the blanched area is termed the capillary refill (CR) test.…”
Section: Introductionmentioning
confidence: 99%